Synthesis of silver nanoparticles by Clinacanthus nutans extract supported with identification of flavonoids by UPLC QTOF/MS and its antimicrobial activity - Zulkifli, Farah Hanani (2019)
The present study reported a simple, environmental-benign and cost effective method in synthesizing silver nanoparticles (AgNPs) by using Clinacanthus nutans methanolic extract at 37oC. The reduction of silver ions could be visually observed as indicated by the developed of light reddish brown colour after incubation period of 1 h. The synthesized AgNPs was further monitored by UV-visible spectroscopy. A characteristic surface plasmon resonance (SPR) band was showed at around 480 nm in UV-vis spectrum and the intensity was increased with the increased of volume ratio of plant extract and incubation period. The characterization of the AgNPs in terms detailed size and morphology was performed by Field Emission Scanning Electron Microscopy (FESEM). The FESEM micrograph revealed that AgNPs were in the size range of 77.8-85.3 nm and spherical in shape. Next, Energy Dispersive X-ray spectroscopy (EDX) was conducted and further confirming presence of elemental silver as indicated by the signal peak at 3 keV. With respect to Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) analysis, reduction of silver ions was remarkably indicated by decreased in intensities of several significant functional groups including C-N stretch, C-O stretch, C=C stretch, C-H stretch and C=O stretch. Furthermore, antibacterial activity of biosynthesized AgNPs shows effective inhibition against common pathogen bacterial strains including Bacillus subtilis, Enterococcus faecalis, Escherichia coli and Pseudomonas aeruginosa. Ultra Performance Liquid Chromatography (UPLC)- Quadrupole Time-Of-Flight (QTOF) was conducted to investigate active metabolites in C. nutans methanolic extract and the results revealed that polyphenolic compounds including flavonoids and phenolic groups present in C.nutans were mainly responsible for the reduction and stabilization of AgNPs.